Practice recommendations regarding parental presence in NICUs during pandemics caused by respiratory pathogens like COVID-19 - Campbell-Yeo, Marsha; Bacchini, Fabiana; Alcock, Lynsey; Mitra, Souvik; MacNeil, Morgan; Mireault, Amy; Beltempo, Marc; Bishop, Tanya; Campbell, Douglas M.; Chilcott, Addie; Comeau, Jeannette L.; Dol, Justine; et al. (Frontiers in Pediatrics, 2024)
Aim: To co-create parental presence practice recommendations across Canadian NICUs during pandemics caused by respiratory pathogens such as COVID-19 Methods: Recommendations were developed through evidence, context, Delphi and Values and Preferences methods. For Delphi 1 and 2, participants rated 50 items and 20 items respectively on a scale from 1 (very low importance) to 5 (very high). To determine consensus, evidence and context of benefits and harms were presented and discussed within the Values and Preference framework for the topranked items. An agreement of 80% or more was deemed consensus. Results: After two Delphi rounds (n=59 participants), 13 recommendations with the highest rated importance were identified. Consensus recommendations included 6 strong recommendations (parents as essential caregivers, providing skin-to-skin contact, direct or mothers' own expressed milk feeding, attending medical rounds, mental health and psychosocial services access, and inclusion of parent partners in pandemic response planning) and 7 conditional recommendations (providing hands-on care tasks, providing touch, two parents present at the same time, food and drink access, use of communication devices, and in-person access to medical rounds and mental health and psychosocial services). Conclusion: These recommendations can guide institutions in developing strategies for parental presence during pandemics caused by respiratory pathogens like COVID-19